Integrating indigenous traditional knowledge and ergonomic efficiency for sustainable millets farming: a study from Koraput, Odisha, India - Chapke, Rajendra R.; Satyavathi, C. Tara; Babu, K. Srinivasa; Laxmiprasanna, Peddiveeti (Frontiers in Sustainable Food Systems, 2025)
Millets offer significant potential for sustainable agriculture in tribal regions, yet the role of Indigenous Traditional Knowledge and the ergonomic burden on farmers, particularly women remain underexplored. This study addresses these gaps by examining the interplay between Indigenous Traditional Knowledge, physical drudgery, and millet farming practices in Koraput, Odisha. Despite wide use of ecologically sound traditional methods, farmers especially women face substantial drudgeries in post-harvest tasks such as threshing, de-hulling, and grinding. A mixed-methods approach was used to collect data from 100 randomly selected tribal farmers across three villages through structured interviews, key informant interviews, focus group discussions, and field observations. The human physical drudgery index was applied to assess ergonomic risks. Findings showed that traditional practices, while sustainable, impose very high physical strain in case of threshing (Drudgery Index = 84.63) and flour making (Drudgery Index = 71.62), ranked as the most drudgery-intensive operations. Improved tools significantly reduced the human physical drudgery index but were underutilized due to affordability, limited access, and cultural preferences. The study highlights the need to integrate validated indigenous traditional knowledge with gender-sensitive ergonomic innovations to enhance sustainability and farmer wellbeing. Policy measures should focus on self-help groups led and or custom hiring services of the machinery, expanding participatory extension, and subsidies for women-friendly equipment. Reducing drudgery while preserving traditional knowledge is key to resilient and inclusive millet-based farming systems.